Effect of a calcium-phosphate based desensitizer on dentin surface characteristics - Ornnicha Thanatvarakorn (2018)
This study aimed to evaluate the ability of a newly developed calcium-phosphate desensitizer in dentin permeability reduction and its integration with dentin surface before and after immersion in artificial saliva (AS) under two different dentin surface characteristics; with or without the collagen exposure. Human dentin discs treated by EDTA to expose collagen fibrils or EDTA/NaOCl to expose plain dentin surface were subjected to a calcium-phosphate desensitizer (Teethmate Desensitizer; TMD), while non-desensitizer treatment served as control. TMD application showed the occlusion in dentinal tubules and reduction in dentin permeability up to 92%, regardless of dentin surface characteristics. After AS immersion, permeability reduction percent (PR%) significantly increased in EDTA/NaOCl pretreatment (p<0.05). Newly-formed crystallites were observed on desensitizer treated dentin and EDTA/NaOCl pretreatment control group, whereas the crystallites did not exist on EDTA pretreatment control group. Ultrasonication revealed the integration of the calcium-phosphate rich layer of desensitizer on dentin surface after AS immersion.